2015
DOI: 10.18191/2015-08-2-027
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins from Lactic Acid Bacteria: A Review of Biosynthesis, Mode of Action, Fermentative Production, Uses, and Prospects

Abstract: Abstract-Bacteriocins are antimicrobial peptides that help bacteria fight competing bacteria in microecological systems. Bacteriocins of lactic acid bacteria (LAB) have attracted much interest in recent years because of their properties that make them suitable as natural food preservatives against specific food pathogens, and as possible supplement to antibiotics against drug resistant bacterial strains. LAB bacteriocins are generally classified into the lantibiotics and non-lantibiotics, the latter divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
0
32
0
1
Order By: Relevance
“…Modification of LAB strains and optimization of process parameters, such as temperature, pH, and media composition have been reported to be cost effective and to increase the yield of bacteriocins (Abbasiliasi et al., ; Garsa, Kumariya, Sood, Kumar, & Kapila, ). The genes responsible for bacteriocin biosynthesis are generally clustered together with structural cognate immunity genes (Perez, Perez, & Elegado, ). Bacteriocins are typically synthesized as biologically inactive precursors, containing a modifiable N‐terminal leader peptide attached to the C‐terminal propeptide (Perez et al., ).…”
Section: Chitosan and Chitooligosaccharidementioning
confidence: 99%
See 1 more Smart Citation
“…Modification of LAB strains and optimization of process parameters, such as temperature, pH, and media composition have been reported to be cost effective and to increase the yield of bacteriocins (Abbasiliasi et al., ; Garsa, Kumariya, Sood, Kumar, & Kapila, ). The genes responsible for bacteriocin biosynthesis are generally clustered together with structural cognate immunity genes (Perez, Perez, & Elegado, ). Bacteriocins are typically synthesized as biologically inactive precursors, containing a modifiable N‐terminal leader peptide attached to the C‐terminal propeptide (Perez et al., ).…”
Section: Chitosan and Chitooligosaccharidementioning
confidence: 99%
“…The genes responsible for bacteriocin biosynthesis are generally clustered together with structural cognate immunity genes (Perez, Perez, & Elegado, 2015). Bacteriocins are typically synthesized as biologically inactive precursors, containing a modifiable N-terminal leader peptide attached to the C-terminal propeptide (Perez et al, 2015). This inert substance is transformed into an active bacteriocin after undergoing an enzymatic process, known as bacteriocin maturation (Riley & Wertz, 2002), before it is transported out of the cell.…”
Section: Production Of Bacteriocinsmentioning
confidence: 99%
“…There are two International Journal of Polymer Science killing mechanisms aiming at the properties of bacterial cell membrane [31]. At lower concentrations, nisin molecule is binding to lipid II, which has a role in correct cell wall synthesis and its blocking that causes the cell death.…”
Section: Testing Of Nisin Antibacterial Activity In the Lyophilisatesmentioning
confidence: 99%
“…The previous studies have shown a relationship between the amount of lipoteichoic acid in the cell wall of Gram-positive bacteria (G+) and increased pediocin activity against G+ bacteria. There is higher pediocin activity when the acid concentration is increased in the walls of bacterial cells [ 27 , 28 ]. This result agrees with the previous statement, in which pediocin was evaluated as low-molecular-weight (2.7-17 KDa) cationic molecules.…”
Section: Discussionmentioning
confidence: 99%